Digital Imaging Analysis for the Study of Endotoxin-Induced Mitochondrial Ultrastructure Injury - Mandar S. Joshi; Elliott D. Crouser; Mark W. Julian; Brandon L. Schanbacher; John Anthony Bauer (Analytical Cellular Pathology)
Primary defects in mitochondrial function have been implicated in over 100 diverse diseases. In situ, mitochondria possess unique and well-defined morphology in normal healthy cells, but diseases linked to defective mitochondrial function are characterized by the presence of morphologically abnormal and swollen mitochondria with distorted cristae. In situ study of mitochondrial morphology is established as an indicator of mitochondrial health but thus far assessments have been via subjective evaluations by trained observers using discontinuous scoring systems. Here we investigated the value of digital imaging analysis to provide for unbiased, reproducible, and convenient evaluations of mitochondrial ultrastructure. Electron photomicrographs of ileal mucosal mitochondria were investigated using a scoring system previously described by us, and also analyzed digitally by using six digital parameters which define size, shape, and electron density characteristics of over 700 individual mitochondria. Statistically significant changes in mitochondrial morphology were detected in LPS treated animals relative to vehicle control using both the subjective scoring system and digital imaging parameters (p < 0:05). However, the imaging approach provided convenient and high throughput capabilities and was easily automated to remove investigator influences. These results illustrate significant changes in ileal mucosal mitochondrial ultrastructure during sepsis and demonstrate the value of digital imaging technology for routine assessments in this setting.